قتل الغيلة بين الحرابة والقصاص - جندب، أحمد علي (جامعة الأندلس للعلوم والتقنية, 2019)
In this research, the subject of Algilah killing (assassination) has been discussed from different aspects: its concept, types, legitimacy and the Fiqih adaptation. There are tow opinions in Fiqih adaptation for Algilah killing; the first states that assassination is a type of Hirabah's Crime, so it takes Hirabah’s penalty. The seconed states that assassination is a type of purposely killing, so it takes penalty of Qessas. There for inheritor can forgive a killer. Both opinions have been discussed in this research. Then, the preponderant opinion has been inspected. In addition, the definition and properties of Hudod and Qessas have been explored as well as the opinion of Yemeni's law. After that, the political assassination has been discussed in addition to other related issues. Finally, the research reached the following conclusions and recommendations: Al Gilah Killing belongs to Al-Hudod in Islamic jurisprudence and it takes penalty of Hirabah, so nobody have the right of forgiveness on this crime. This is the opinion of Al-Emam Malek and the research is compatibale with Al-Emam Malek opinion and recommended it, because it is effective to thwart these crimes. In addition, the research recommended to take in consideration the collective Ejtehad in respect of creation of suitable opinions for contemporaneous crimes.
تناول البحث "قتل الغيلة" من حيث مفهومه وصوره، وحكمه، والتكييف الفقهي له بين القول بأنه صورة من صور الحرابة فيأخذ عقوبتها الحدية مع ما يترتب عليها من أحكام، وبين القول بأنه صورة من صور القتل العمدي فيأخذ عقوبة القصاص مع ما يترتب عليها من أحكام، ثم الترجيح بين القولين. كما يتناول الاغتيال السياسي كأبرز صور الغيلة، ثم بعض المسائل المتفرقة. وخلص البحث في الخاتمة إلى أن قتل الغيلة حد من حدود الله يأخذ حكم الحرابة، فيقتل المغتال حدا لا قصاصا وليس لولي الدم ولا لغيره العفو عنه. وهو رأي المذهب المالكي، الذي أوصى البحث بالأخذ به في قتل الغيلة لفعاليته في حسم هذا النوع من الجرائم، كما أوصى بتفعيل الاجتهاد الجماعي لإيجاد الأحكام المناسبة للمسائل الفقهية المعاصرة.
Keywords: القانون الجنائي -- الفقه الإسلامي -- جرائم القتل -- القوانين والتشريعات